Extreme hardness at high temperature with a lightweight additively manufactured multi-principal element superalloy. (December 2022) - Kustas, Andrew B.; Jones, Morgan R.; DelRio, Frank W.; Lu, Ping; Pegues, Jonathan; Singh, Prashant; Smirnov, A.V.; Tiarks, Jordan; Hintsala, Eric D.; Stauffer, Douglas D.; Román-Kustas, Jessica K.; Abere, Michael; et al.
Highlights: Additive manufacturing was utilized to produce light-weight AlMoNbTaTiZr multi-principal-element superalloy parts. The alloy was characterized by a complex structure that enabled temperature-insensitive high-hardness up to 800 °C. Density functional theory informed the alloy microstructure and the resultant temperature-insensitive hardness properties. The value proposition of combining advanced (additive) manufacturing with advanced alloy design tools is discussed. Abstract: Materials are needed that can tolerate increasingly harsh environments, especially ones that retain high strength at extreme temperatures. Higher melting temperature alloys, like those consisting primarily of refractory elements, can greatly increase the efficiency of turbomachinery used in grid electricity production worldwide. Existing alloys, including Ni- and Co-based superalloys, used in components like turbine blades, bearings, and seals, remain a performance limiting factor due to their propensity, despite extensive optimization efforts, for softening and diffusion-driven elongation at temperatures often well above half their melting point. To address this critical materials challenge, we present results from integrating additive manufacturing and alloy design to guide significant improvements in performance via traditionally difficult-to-manufacture refractory alloys. We present an example of a multi-principal element alloy (MPEA), consisting of five refractory elements and aluminum, that exhibited high hardness and specific strength surpassing other known alloys, including superalloys. The alloy shows negligible softening up to 800°C and consists of four compositionally distinct phases, in distinction to previous work on MPEAs. Density functional theory calculations reveal a thermodynamic explanation for the observed temperature-independent hardness and favorability for the formation of this multiplicity of phases. Graphical abstract: Image, graphical abstract